2015
DOI: 10.1103/physrevlett.114.195901
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Anharmonicity in fcc Materials: From its Origin toab initioStrategies beyond the Quasiharmonic Approximation

Abstract: We derive the Gibbs energy including the anharmonic contribution due to phonon-phonon interactions for an extensive set of unary fcc metals (Al, Ag, Au, Cu, Ir, Ni, Pb, Pd, Pt, Rh) by combining density-functional-theory (DFT) calculations with efficient statistical sampling approaches. We show that the anharmonicity of the macroscopic system can be traced back to the anharmonicity in local pairwise interactions. Using this insight, we derive and benchmark a highly efficient approach which allows the computatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(110 citation statements)
references
References 27 publications
4
104
2
Order By: Relevance
“…Lattice anharmonicity is also known to cause deviations from an Arrhenius temperature-dependent behavior for thermodynamic and kinetic properties in bulk systems. For example, it is known that vacancy formation [106,107] and migration (or diffusion, i.e., defect formation + defect migration) energies [108][109][110] may vary considerably from 0 K up to the melting temperature. Molecular dynamics simulations inherently resolve the problems mentioned above by integrating Newton's equations of motion for each atom at any temperature of interest.…”
Section: Finite-temperature Aimd Resultsmentioning
confidence: 99%
“…Lattice anharmonicity is also known to cause deviations from an Arrhenius temperature-dependent behavior for thermodynamic and kinetic properties in bulk systems. For example, it is known that vacancy formation [106,107] and migration (or diffusion, i.e., defect formation + defect migration) energies [108][109][110] may vary considerably from 0 K up to the melting temperature. Molecular dynamics simulations inherently resolve the problems mentioned above by integrating Newton's equations of motion for each atom at any temperature of interest.…”
Section: Finite-temperature Aimd Resultsmentioning
confidence: 99%
“…The insensitivity of high-temperature vibrations to nonlocal many-body effects is remarkable since recent studies [22] showed that close to melting the displacement of atoms from their equilibrium positions is significant and that the first-neighbor distance distribution is strongly affected by anharmonicity. Knowing that the GGA-PBE deficiency is not related to thermal vibrations but rather to the T = 0 K energy surface indicates a possible route for the development of accurate ab initio databases.…”
Section: Fig 2 (Color Online)mentioning
confidence: 99%
“…Recent work [22] showed that explicit anharmonicity can partly compensate the quasiharmonic heat capacity. As shown in Fig.…”
Section: Fig 2 (Color Online)mentioning
confidence: 99%
“…This is indeed associated with temperature variations of the vibrational entropy in the plane orthogonal to the migration path. Lattice vibrations are known to affect the shape of the effective potential energy landscape, especially at temperatures close to melting [49,50,96]. A separate quantification of the effects of harmonic and anharmonic vibrations on temperature-induced variations in migration energies is a challenging research topic that deserves thoughtful investigation.…”
Section: B Ti Vacancy Equilibrium Jump Ratesmentioning
confidence: 99%
“…Kinetic properties are extrapolated to finite temperatures using transition state theory (TST) [44] by assuming essentially fully harmonic lattice vibrations, or employing quasiharmonic approximations [45,46]. These approaches, however, are not applicable to crystal phases which are unstable at 0 K (e.g., Group-VB TM nitrides [47,48]) and may yield inaccurate predictions when the role of anharmonic lattice vibrations becomes relevant [49][50][51]. Quantitatively reliable evaluation of kinetically controlled properties at given temperatures and pressures of interest necessarily requires the use of computer simulations reproducing atomic trajectories.…”
Section: Introductionmentioning
confidence: 99%